Caladenia virus A, an unusual new member of the family Potyviridae from terrestrial orchids in Western Australia - Wylie, S.; Tan, A.; Li, H.; Dixon, Kingsley; Jones, M. (2012)
An isolate of a new virus, Caladenia virus A (CalVA), was identified infecting Australian terrestrial orchids. The complete genome of 9,847 nucleotides encodes 11 gene products typical of most members of the family Potyviridae. Sequence comparisons of the polyprotein revealed that CalVA shared highest sequence identity (37.5-39.6 %) with members of the genus Poacevirus. Although a vector for CalVA was not identified, a mite transmission motif was present in the helper component protease, indicating that, like other poaceviruses, mites may transmit it. CalVA is the only proposed member of the genus Poacevirus not isolated from a poaceous host.